Improving Training Technologies for Beginner Athletes In Kurash During the Initial Preparation Stage - Kaniyazov, Sultaniyaz; Allaniyazov, Nazbibi (Indonesian Journal Publisher, 2025)
This study investigates the modernization of training technologies for beginner athletes in kurash, focusing on the initial preparation stage where fundamental technical, physical, tactical, and psychological foundations are established. As a national style of upright wrestling originating from Central Asia, kurash requires rapid balance adjustment, precise gripping actions, explosive force generation, and refined biomechanical control. Traditional kurash training methods heavily emphasize repeated throwing drills and general strength work, often overlooking motor learning principles and individualized adaptation for beginners. Using a theoretical–analytical research design, this study synthesizes findings from kurash pedagogy, biomechanics, motor control, and contemporary training technologies to identify effective developmental strategies. The results show that progressive training technologies—such as visual feedback systems, movement analysis tools, dynamic balance training, modified kurash tasks, reaction and anticipation drills, and coordination-based conditioning—significantly enhance beginners’ technical acquisition, movement stability, and tactical understanding. The study concludes that integrating modern technologies with traditional kurash methodology offers a more efficient, safer, and scientifically grounded pathway for developing novice kurash athletes, forming a strong foundation for future competitive performance.